Strategic Workforce Transformation and Hybrid Work Culture: An Empirical Study of Corporate HR Practices in Korba, Chhattisgarh - Bal Kishore Jaiswal; Dr. Arvind Kumar Saxena (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The transformation of traditional workplace dynamics, accelerated by global disruptions, has led to the emergence and adoption of hybrid work models, blending remote and in-office operations. This study investigates the strategic implications of hybrid work on human resource (HR) management, employee productivity, and organizational effectiveness, specifically in the corporate sector of Korba. It aims to evaluate the perception of employees toward inclusion, access to resources, communication flow, and HR-related challenges within the hybrid work environment. The research also explores the influence of hybrid strategies on employee retention and the extent of organizational preparedness in terms of infrastructure, policy clarity, and managerial capability. Using a structured questionnaire, primary data were collected from 384 respondents across various corporates operating in Korba. Descriptive statistics, correlation analysis, ANOVA, and regression models were applied to test the formulated hypotheses. The findings reveal that strategic HR practices have a significant relationship with the successful implementation of hybrid work. Additionally, the hybrid work model positively impacts employee satisfaction and productivity, although challenges related to supervision, engagement, and professional isolation persist. A notable difference in HR challenges was observed across different work setups fully remote, hybrid, and traditional models. The study concludes that while hybrid work offers flexibility and enhanced performance potential, its success is contingent upon adaptive HR policies, robust digital infrastructure, and inclusive organizational practices. Based on the results, several recommendations are proposed, including strengthening HR frameworks, enhancing communication, fostering mental well-being, investing in digital tools, and promoting employee participation in policy-making. These strategies not only help mitigate challenges but also facilitate sustainable workforce transformation in the post-pandemic era. This research contributes to the growing body of literature on hybrid work culture and serves as a practical guide for HR leaders and decision-makers aiming to optimize hybrid work frameworks in regional corporate settings.